2018
DOI: 10.1177/0145445518764343
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Inappropriate Use of Mobile Devices in Urban High School Classrooms: Comparing an Antecedent Intervention With and Without the Good Behavior Game

Abstract: As the capabilities of portable technology continue to advance and become more accessible, educators express concern about the impact of the inappropriate use of mobile devices on academic engagement and learning. An alternating treatments design was used to compare the effectiveness of an antecedent (Clear Box) intervention and an interdependent group contingency (Clear Box + Good Behavior Game [GBG]) intervention to typical classroom management techniques (Control) in increasing the academic engagement and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
(39 reference statements)
1
14
1
1
Order By: Relevance
“…Unlike prior studies of adolescents in typical school settings (Hernan et al, 2018; Kleinman & Saigh, 2011) and in residential treatment facilities (Brogan, Falligant, et al, 2017; McDougale et al, 2018), the current study showed that rules plus feedback about rule violations decreased adolescents’ problem behavior in three classroom settings. The social validity measures show a general satisfaction with the procedures across all classrooms.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…Unlike prior studies of adolescents in typical school settings (Hernan et al, 2018; Kleinman & Saigh, 2011) and in residential treatment facilities (Brogan, Falligant, et al, 2017; McDougale et al, 2018), the current study showed that rules plus feedback about rule violations decreased adolescents’ problem behavior in three classroom settings. The social validity measures show a general satisfaction with the procedures across all classrooms.…”
Section: Discussioncontrasting
confidence: 94%
“…In particular, students in C3 consistently displayed high rates of problem behavior during baseline sessions. Moreover, the change in class size captured in this study was common to many classrooms within the residential facility, as well as with other studies with groups of adolescents (e.g., Hernan et al, 2018; McDougale et al, 2018). The fact that the intervention exerted consistent effects across inconsistent and novel members of the classroom supports the generality of behavior changes produced by posting rules.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Moser, Schoenebeck, dan Reinecke (2016) yang meneliti keberadaan ponsel dalam konteks makan bersama juga memberikan arahan bagi penelitian selanjutnya bahwa perlu adanya upaya untuk mengelola penggunaan ponsel pada waktu makan bersama. Adapun pelaksanaan intervensi berkaitan dengan penggunaan ponsel yang dapat mengganggu aktivitas lain, pada penelitian sebelumnya dilaksanakan di lingkungan sekolah (Hernan, Collins, Morrison, & Kroeger, 2018) dan saat mengendarai mobil di jalan umum (Clayton & Myers 2008).…”
Section: Pendahuluanunclassified